Modus Darwin Reconsidered. (7th July 2016) - Helgeson, Casey
ABSTRACT: 'Modus Darwin' is the name given by Elliott Sober to a form of argument that he attributes to Darwin in the Origin of Species, and to subsequent evolutionary biologists who have reasoned in the same way. In short, the argument form goes: similarity, ergo common ancestry. In this article, I review and critique Sober's analysis of Darwin's reasoning. I argue that modus Darwin has serious limitations that make the argument form unsuitable for supporting Darwin's conclusions, and that Darwin did not reason in this way. 1 Introduction 2 Modus Darwin 3 Limitations of Sober's Formal Framework 3.1 Anatomical space 3.2 Branch lengths 4 Did Darwin Use Modus Darwin? 4.1 Adaptive characters 4.2 Galapagos 5 Modus Darwin versus Phylogenetic Inference 6 Conclusion